Effect of round robin instructional approach on development of students’ mathematical skills in secondary schools - Nwoke, Bright Ihechukwu (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2025)
Abstract The study investigated the effect of round robin instructional strategy on development of students’ mathematical skills in secondary schools. The study was carried out in secondary schools in Ngor Okpala Local Government Area of Imo State, Nigeria. Three research hypotheses guided the study based on the objectives. The study was a quasi-experimental research type adopting the pre-test, posttest non equivalent control design. The instrument for data collection was a researcher made test titled “Mathematics achievement test MAT”. The instrument had reliability coefficient of 0.75 determined using persons product Moment Correlation Coefficient (PPMC). The experiment group was taught using round robin instructional strategy, while the control group was taught using conventional approach.  The data generated were analyzed using ANCOVA to test the hypotheses at 0.05 level of significance. The results of the study showed that the round robin instructional strategy increases students' mathematics achievement. No significant difference was found between the achievement scores of male and female students taught mathematics using the round robin instructional strategy. It was recommended that secondary school mathematics teachers should try to use round robin instructional strategies to teach mathematics in order to increase students’ achievement.